Acoustic properties of model cellular vitreous carbon foams. (August 2017) - Letellier, M.; Ghaffari Mosanenzadeh, S.; Naguib, H.; Fierro, V.; Celzard, A.
Abstract: This paper deals with the relations between structural and acoustic properties of model vitreous carbon foams, i.e., presenting different porous structures in terms of bulk density, cell size and connectivity, while having the same composition and the same carbon texture. This is a major achievement with respect to former studies, in which foams had cell sizes directly correlated to their total porosity, thus preventing the independent analysis of these two parameters. The permeability k 0 and the absorption coefficients A of these new carbon foams were studied in relation to their porous structures. k 0 was controlled by cell diameter, and an absorption optimum is expected in the range 1 × 10 − 9 m ² < k 0 < 3 × 10 − 9 m ² . A also increased with porosity but to a lesser extent. Cellular foams had absorption peaks whose amplitude and selectivity varied greatly. A model considering foams as combinations of Helmholtz resonators in parallel was used to highlight that these peaks correspond to the resonance of the whole samples, notably related to the smallest windows present in the cell walls. Thus, it was found that the cell size controls the permeability and hence the sound absorption, but the resonance of the carbon framework may be tailored through the window size distribution. Graphical abstract: